Os carnavais da revanche: ordenamentos biopolíticos nas produções de sentido sobre os carnavais cariocas das pandemias da gripe espanhola e Covid-19 - Alahmar, Luana de Carvalho (2023)
In this work, we approach the interrelationships between communication, disciplinary practices and biopolitical orders present in the production of meanings related to pandemics and the Carioca Carnival in two moments: after the outbreak of the Spanish Flu (1918/1919) and Covid-19, (2021/2022). To this end, we defined the following problem question: How does the production of meanings about the carioca carnivals of the aforementioned pandemics take place, considering permanencies and displacements with regard to biopolitical orders, with a focus on disciplinary practices? The corpus is composed of artistic materials (marchinhas, names of blocks and the samba plot of the Unidos da Viradouro school in 2022); journalistic materials (newspaper headlines that explain disciplinary practices in carnivals); and publicity materials, which illustrate disciplinary practices in the analyzed periods. As for the theoretical foundation, scholars of consumption and communication were mobilized, such as Douglas Kellner, Roger Silverstone, Isleide Fontenelle, Everardo Rocha. For reflections on Discipline, Biopolitical Orders and the Pandemic, we mobilized the following authors: Michel Foucault, Tânia Hoff, Mikhail Bakhtin, Ruy Castro, David Butter, Roberto da Matta, Liane Bertucci and Felipe Ferreira.